Repenser Les Limites : L’architecture À Travers L’espace, Le Temps Et Les Disciplines 2005
DOI: 10.4000/books.inha.2509
|View full text |Cite
|
Sign up to set email alerts
|

Controverses autour de l’axe héliothermique : l’apport de la simulation physique à l’analyse des théories urbaines

Abstract: Spatialization of the political and social gives architectural and urban structures a particular form of agency. In the organization, use, and representation of space in architecture social and spatial practices would seem most clearly to intersect with each other and with the dynamics of history. Henri Lefebvre described the relationship among spatiality, historicality, and sociality in terms of "une dialectique de triplicité", a

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Rey analysed the winter sun's path for several cities and correlated the different land areas' consumptions in relation to north-south and east-west blocks' orientations. His knowledge of the daily difference in the time it took to reach the maximum solar radiation and the maximum air temperature-la vague thermiqueled Rey together with Barde and Pidoux, to develop the heliothermic theory [62], «qui prétend rendre compte de «l'échauffement» des bâtiments en tenant compte à la fois de leur exposition au soleil et de la température de l'air» [63]. The wide dissemination of the heliothermic axis influenced the work of several important designers, such as Le Corbusier, who presented at the third CIAM in Brussels his plan for the Ville Radieuse, which was oriented by 19 northeast degrees [64].…”
Section: Bioclimatism In the European Modern Movementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rey analysed the winter sun's path for several cities and correlated the different land areas' consumptions in relation to north-south and east-west blocks' orientations. His knowledge of the daily difference in the time it took to reach the maximum solar radiation and the maximum air temperature-la vague thermiqueled Rey together with Barde and Pidoux, to develop the heliothermic theory [62], «qui prétend rendre compte de «l'échauffement» des bâtiments en tenant compte à la fois de leur exposition au soleil et de la température de l'air» [63]. The wide dissemination of the heliothermic axis influenced the work of several important designers, such as Le Corbusier, who presented at the third CIAM in Brussels his plan for the Ville Radieuse, which was oriented by 19 northeast degrees [64].…”
Section: Bioclimatism In the European Modern Movementmentioning
confidence: 99%
“…The axis's effectiveness was disputed during the 1940s; it opposed the "hygienists", the partisans of east-west exposure, to the "climatologists", who were advocates of southern exposure, among whom was Vinaccia (1943), who counterposed his equisolare orientation theory [65]. Even though Vinaccia did not have available contemporary tools to demonstrate the correctness of his opinion, it is interesting to highlight (as recent research has confirmed) the inefficacy of Rey's theory [63,66].…”
Section: Bioclimatism In the European Modern Movementmentioning
confidence: 99%
“…Ces projets participent d'une même idée générale : il ne s'agit pas encore d'orienter les façades et les fenêtres vers le soleil, mais de faciliter le drainage lumineux du ciel vers la ville, par la construction de ce que l'on peut décrire comme des entonnoirs à lumière et des canaux lumineux. (Harzallah, 2005 ;Siret, 2006). 14 Au delà des questions d'orientation, le tournant héliotrope marque une transformation importante de l'architecture ordinaire (Medici, 2003 ;Campbell, 2005 transformer.…”
unclassified
“…Les préconisations des auteurs portent souvent sur la forme urbaine (Siret & Harzallah, 2006). L'orientation des voies se fait selon l'axe héliothermique ; axe de symétrie thermique qui prend en compte températures d'air et durées d'insolation (Harzallah et al, 2005). Rey (et al, 1928) établit qu'au nom de l'égalité héliothermique des façades, l'orientation optimale des bâtiments se situerait autour de 20° par rapport à l'axe nord-sud.…”
Section: Historique Des Interrelations Entre Architecture Et Santéunclassified